2010 IEEE International Conference on Image Processing 2010
DOI: 10.1109/icip.2010.5649265
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual image quality assessment using a geometric structural distortion model

Abstract: The goal of image quality assessment research is to design quantitative measurements for the evaluation of image quality such that it is consistent with subjective human evaluation. Inspired by intrinsic geometric structure of nature images and characteristic of visual perception, we propose a novel geometric structural distortion model for image quality assessment in this paper, which has relatively low computational complexity and clear physical meanings. The experimental results of LIVE image database show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…However, HVS is too complex and our current knowledge about it is far from enough to construct an accurate bottom-up IQA framework. The second strategy adopts a top-down framework [3,30,[4][5][6][7][8], which aims to model the overall function of HVS based on some global assumptions on it. Many FR-IQA models follow this framework.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, HVS is too complex and our current knowledge about it is far from enough to construct an accurate bottom-up IQA framework. The second strategy adopts a top-down framework [3,30,[4][5][6][7][8], which aims to model the overall function of HVS based on some global assumptions on it. Many FR-IQA models follow this framework.…”
Section: Introductionmentioning
confidence: 99%
“…Other state-of-the-art FR-IQA models that follow the top-down framework include Ratio of Non-shift Edges (rNSE) [18,24], Feature SIMilarity (FSIM) [7] comprehensive survey and comparison of state-of-the-art IQA models can be found in [30,14]. Aside from the two different strategies for FR-IQA model design, many IQA models share a common two-step framework [16,[4][5][6][7][8], as illustrated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, HVS is too intricate to construct an accurate bottom-up FR-IQA framework. The second one constructs a top-down framework [8][9][10][11] which designs to model the overall function of HVS according to some global assumption. Recent studies [8,9] have demonstrated the effectiveness of these kinds of methods, and thus, many approaches follow the top-down framework.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a great deal of researches on image compression have been carried out, and many image coding technologies and standards have been developed [4][5][6][7]. These coding techniques mainly involve the image compression technology based on the human visual and auditory characteristics, wavelet transform theory, and fractal theory [8][9][10][11][12][13]. However, the contrast sensitivity characteristics of the human visual system (HVS) have not been exploited much in the field of color image compression [1][2][3].…”
Section: Introductionmentioning
confidence: 99%